Impact of the Factors of National Competitive Advantage on the Development of the Polish Furniture Industry - Wiśniewski, Dariusz (Studia Oeconomica Posnaniensia, 2013)
This article discusses the national factors that may affect the country’s competitive advantage in the furniture industry. Based on Porter’s Diamond model, it presents a set of specific conditions that characterize the Polish furniture industry, the identification of which made it possible to relate to the hypothesis posed in the article. A favourable combination of factors that determine the national competitive advantage affects the current position of the industry, which has the potential to become a national industry recognized in demanding foreign markets. The factors presented contribute towards the attractiveness of a country as a market for sales and as a place for actions which increase added value.